(untitled) (Journal of Parents and Teachers, 2014)
PBL is a type of methodology following guided discoveries. PBL is found within the active methodologies. This article talks about the teacher’s role as a mediator, facilitator and coach (avoiding master lectures) and also about the patterns to apply this methodology in class. The problem design is very important because it leads the whole process.